Back close non-syllabic vowel [U] behaviour in European Portuguese: reduction or suppression? - Barros, Maria João (2011)
In this paper we analyse and describe the phonetic behavior of the non-tonic back closed vowel [u] in European Portuguese (EP) in what respects its quality and relative duration. Slow and faster speech was used. The objective of this work is to contribute with experimental results in order to obtain a more accurate comprehension of this vowel’s profile, which can be integrated and extended to other non-tonic vowels’ behaviors in the EP non-tonic vowel system. This may represent an important improvement in synthetic speech quality and naturalness, as it concerns acoustical parameters, rhythm and supra-segmental features, which means prosody. This study is inscribed in a project in Speech Synthesis for EP held by an inter-disciplinary group in intimate articulation between the engineering experience and tools and the linguistic approach.